2022
DOI: 10.3390/diagnostics12122937
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors in Patients with Congenital Hemophilia: A Focus on Hypertension

Abstract: Aging hemophiliacs face cardiovascular disease. Lots of evidence has been gathered that hemophiliacs have a more unfavorable cardiovascular profile than the general population does, especially due to the increased prevalence of hypertension (HTN). Among the existing scattered evidence, our study provides the most comprehensive and systematized analysis of the determinants of HTN in hemophiliacs. We discussed the contribution to the HTN substrate of hemophilia-specific factors, such as type, severity and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…The prevalence of hypertension (≥140/90 mmHg) in Japanese PWH is equal to that of the general population, but studies of Western populations have shown hypertension to be more prevalent in PWH than the general population; incidences of hypertension in PWH may increase as the population of PWH ages 14,19 . PWH are at a much greater risk for developing intracranial haemorrhage (ICH), which is associated with a mortality rate of approximately 20% 19 . ICH occurs most frequently in PWH in young children (≤2 years of age), and adults ≥60 years of age with risk factors such as hypertension 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension (≥140/90 mmHg) in Japanese PWH is equal to that of the general population, but studies of Western populations have shown hypertension to be more prevalent in PWH than the general population; incidences of hypertension in PWH may increase as the population of PWH ages 14,19 . PWH are at a much greater risk for developing intracranial haemorrhage (ICH), which is associated with a mortality rate of approximately 20% 19 . ICH occurs most frequently in PWH in young children (≤2 years of age), and adults ≥60 years of age with risk factors such as hypertension 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The classic arterial vascular risk factors, including hypertension, obesity, diabetes, dyslipidemia, and sedentary lifestyle, which are common in older patients, promote the development atheromatosis in PWH independently of FVIII or FIX deficiency. The high prevalence of hypertension and obesity among PWH has been well‐documented 2,3 . Although the rate of atherosclerosis appears similar in PWH compared with the general population, cardiovascular mortality is reduced.…”
Section: Basal Factor VIII or Ix Levels Duration Of Antithrombotic Tr...mentioning
confidence: 98%
“…The high prevalence of hypertension and obesity among PWH has been well-documented. 2,3 Although the rate of atherosclerosis appears similar in PWH compared with the general population, cardiovascular mortality is reduced. It has been postulated that PWH may be protected from acute coronary syndrome and cardiovascular mortality through increased plaque stability and reduced thrombin generation following plaque rupture.…”
mentioning
confidence: 99%
“…In other nations, particularly in Western countries, it is well-established that hypertension is prevalent among individuals with haemophilia, on the other hand, it has been reported that some studies from Asia suggest a relatively lower prevalence of hypertension. 18,19 The rationale for the equivalent prevalence of hypertension in Japanese individuals with haemophilia and the general Japanese male population remains unclear. It has been proposed that the use of NSAIDs influences conditions such as hypertension and CKD.…”
Section: Myocardial Infarctionmentioning
confidence: 99%